Making Supercapacitors as Teaching Materials for Science Lab Work in High Schools for Supporting the Development of Renewable Energy - Nirwan Syarif; Dedi Rohendi; Supriatini Supriatini (STAI Hubbulwathan Duri, 2022)
This paper reports the results of the development of science lab work teaching materials that focus on the development of renewable energy, especially energy storage devices. The energy storage device discussed was the supercapacitor, including the tools and materials used the manufacturing method and the theory underlying the supercapacitor. The method applied to the development of science lab work teaching materials consists of activity design, subject, data collection and data analysis. The results of data analysis show that the development of labwork teaching materials for senior high schools is suitable for use by educators in science learning based on the assessment of the lecturers / teachers resulting in an assessment with a 95% feasibility percentage (very feasible). Student responses showed that the average number of 86.8% included in the category of very interested. It can be said that the students are very interested in learning to use the material presented. Several recommendations can be given, namely that more plenty and diverse teaching materials are needed in order to make students of high schools can understand the government programs that are being launched and it is necessary to conduct research by teachers and students so that schools can produce students who have capability to enter competition in larger events.